The Effect of the Student Teams Achievement Divisions (STAD) Cooperative Learning Model Assisted by Student Worksheets on the Mathematics Learning Outcomes - Sintiya Fransisca Br Tarigan; Regina Sipayung; Patri Janson Silaban; Darinda Sofia Tanjung; Jhonas Dongoran (International Journal of Research in Education, 2026)
Mathematics learning in elementary schools is often dominated by teacher-centered instruction, resulting in limited student participation and low learning outcomes, particularly in the topic of plane geometry. This study aimed to examine the effect of the Student Teams Achievement Divisions (STAD) cooperative learning model assisted by Student Worksheets (LKPD) on the mathematics learning outcomes of third-grade students at SD Negeri 060973 Medan during the 2025/2026 academic year. This research employed a quantitative approach using a pre-experimental one-group pretest–posttest design. The sample consisted of 28 students selected through total sampling. Data were collected using a mathematics achievement test and a student response questionnaire. Before implementation, both instruments were validated through expert judgment and empirical testing. Item validity was determined using the Pearson Product-Moment correlation by comparing the calculated correlation coefficients with the critical r-value at the 5% significance level, while reliability was assessed using Cronbach's Alpha, with coefficients exceeding 0.70, indicating high reliability. Data were analyzed using descriptive statistics, normality testing, Pearson correlation, the coefficient of determination, and the t-test with IBM SPSS Statistics Version 25. The findings showed that the mean score increased from 52.89 on the pretest to 80.71 on the posttest. The correlation coefficient was 0.804, the coefficient of determination reached 64.64%, and hypothesis testing confirmed a significant positive effect (t = 2.713, p = 0.012). Therefore, the STAD cooperative learning model assisted by Student Worksheets effectively improves elementary students' mathematics learning outcomes.